Interpreting and the clinician : a conversational analysis of the interpreted consultation in a paediatric hospital - Prince, Leyla A (Division of Communication Sciences and Disorders, 2017)
The utilization of interpreters in medical interviews has increasingly become a focus of research, both globally and in South Africa. Effective communication lies at the core of the delivery of a patient-focussed approach to health care and this has been a factor in the drive to improve service delivery, especially from a communication perspective. A number of studies in health care have focussed on the medical interaction between health professionals and their patients. In this study, the aim was to describe and analyse interpreted diagnostic consultations, specifically focussing on the interactions between the health professional, trained interpreter and caregiver. The research was conducted at a tertiary level children's hospital in Cape Town. A qualitative research design was employed in this study. The participants were three health professionals [medical doctors], and a trained interpreter, all employed at a tertiary level children's hospital in the Western Cape, and three caregivers of the children attending the outpatients department. Video recordings of initial assessment consultations were made and thereafter each participant in the consultation, was interviewed. Detailed analysis of the consultations was done using the methods of conversational analysis. Thematic analysis of the post-consultation interviews was done and the findings triangulated with the themes emerging out of the conversational analysis. The findings resulting from the conversational analysis, suggest that interactions taking place in this study could be described as institutional interactions. This was suggested on the basis of the patterns of interactional behaviour, which emerged in the communications of the participants, the interactional strategies used and the interpreter models employed. The need for training for health professionals in interactional strategies also became apparent and highlighted aspects, which may be included in future training of health professionals, which may serve to advance the quality of communication in medical interactions.